Thermodynamic modeling of the Fe−Zn system using exponential temperature dependence for the excess Gibbs energy - Tang Y.; Yuan X.; Du Y.; Xiong W. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The Fe-Zn binary system was re−modeled using exponential equation Li=hi•exp(-T/τi) (i=0,1,2…) to describe the excess Gibbs energy of the solution phases and intermetallic compounds with large homogeneities. A self-consistent set of thermodynamic parameters is obtained and the calculated phase diagrams and thermodynamic properties using the exponential equation agree well with the experimental data. Compared with previous assessments using the linear equation to describe the interaction parameters, the artificial miscibility gap at high temperatures was removed. In addition, the calculated thermodynamic properties of the liquid phase were more reasonable than those resulting from all the previous calculations. The present calculations yield noticeable improvements to the previous calculations.